First‐in‐Man Study of a Novel Peripheral Plaque Atherectomy Device - Hui Wang; Dikang Pan; Shijun Cui; Zhu Tong; Xixiang Gao; Yongquan Gu; Jianming Guo; Lianrui Guo (The Journal of Clinical Hypertension)
ABSTRACT This first‐in‐man (FIM) study evaluated the feasibility and safety of a new peripheral plaque atherectomy system in patients with symptomatic lower extremity artery disease (LEAD). Ten patients with symptomatic LEAD (Rutherford class 2–5) were enrolled in a prospective, single‐center study from March to April 2024. Patients aged 18–85 years with target lesions showing ≥70% stenosis and reference vessel diameters ≥1.8 mm underwent treatment using a novel atherectomy device with a “shaving” mechanism to excise calcified plaques. Outcomes included post‐procedural stenosis improvement, 6‐month primary patency rate, and safety endpoints such as thrombosis, vasospasm, acute occlusion, and distal embolization. Statistical analysis used SPSS 23.0. Ten male patients (mean age: 61.4 ± 9.2 years) were treated. Most had diabetes (80%), hypertension (70%), and hyperlipidemia (80%). Pre‐procedural ankle‐brachial index (ABI) averaged 0.50 ± 0.14. Angiographic analysis showed 60% of lesions in the femoral artery and 40% as chronic total occlusions. No major adverse events occurred, with 100% technical success. Post‐procedural ABI improved to 0.92 ± 0.12 (p < 0.05). At 6 months, the primary patency rate was 100%, with no clinically‐driven revascularization or adverse cardiovascular events. Mortality was 0%. All patients reported significant improvement in symptoms and walking distance, as well as enhanced quality of life and reduced pain during physical activity. The novel atherectomy device showed promising safety and efficacy for treating calcified LEAD. Larger‐scale trials are needed to confirm these outcomes.